PRODUÇÃO DE ÁLCOOL A PARTIR DE RESÍDUO DE MEL SILVESTRE POR FERMENTAÇÃO COM ESCHERICHIA COLI - Leite, Kamila Rodrigues (2017)
In this study, the production of alcohol by fermentation of wild honey residues with Escherichia coli was investigated. The need and interest of new sources of renewable energy and the use of waste such as honey, which is significant in the Center-South of the state of Paraná, makes it necessary to explore the subject. The samples of rusty wild honey were collected from a single supplier from the city of Prudentópolis - PR (25º 12 '47 "S, 50º 58' 40" W) of Multi Flora. For the fermentation, the first method applied was the semi-anaerobic with Erlenmeyer system, evaluating the alcohol production over time from 0 to 72 hours of fermentation with 10% V / V of E. coli. After the oxidized honey D was evaluated in the fermentation from 0 to 120 hours. The obtained alcohols were analyzed by Fourier Transform Infrared Spectroscopy (FTIR). All the residual samples obtained a positive result for alcohol production, in which the residual sample (D) stands out. When comparing the fermentation times employed for this method, it was observed that there was a decline in production after 72 hours of fermentation, up to 120 hours, related to the presence of secondary metabolites of the fermentation process of the sample and also the temperature of the process. The comparisons of the results of the fermentation methods were important to observe that the resulting alcohol samples varied according to the method used, being the most efficient method the system in an anaerobic chamber with erlenmeyer. Through the characterization of alcohol by FTIR, the organic compounds were identified and ethanol PA spectra were detected, reaffirming the efficiency of the method in an anaerobic chamber system with erlenmeyer in terms of quality.